(untitled) (Journal of Dhaka Medical College, 2020)
Context: Adequate knowledge about nutritional status of a community is necessary to have a comprehensive idea about its development process, as under-nutrition is one of the major health problems in developing countries. As an individual’s height and weight can be readily and inexpensively measured, body mass index (BMI) has become a popular heuristic approximation for body fatness in epidemiology and clinical practice. The BMI is the most common surrogate measure of obesity as well as nutritional assessment for individual. For this reasons an attempt has been taken to assess the nutritional status through the body mass index (BMI) among first year students of MBBS and B sc nursing course of government medical education institutes in Dhaka. Material and Methods: This descriptive type of analytic study was conducted in the Anatomy Department of Dhaka Medical College, Dhaka. The study sample was 177 individuals of first year students of MBBS and B.Sc nursing course admitted in the session of 2017-2018 in the Dhaka Medical College & Dhaka Nursing College, Dhaka. Body Mass Index (BMI) was calculated as student’s weight in kilograms divided by the square of the student’s height in meters (kg/m2). The warning sign of poor nutritional health was calculated according to the checklist adapted by the Nutrition Screening Initiative, American Academy of Family Physicians July 2001. With the help of statistical software SPSS-20 comparisons between the two groups were done. Result: The mean (±SD) height (meter), weight (kg) and BMI of groups MBBS and B Sc nursing were 1.63±0.09, 61.65±11.22, 23.11±3.53 and 1.56±0.07, 49.05±9.42, 20.15±3.47 respectively. Good nutritional health status was found 61.80% in MBBS and 53.30% in B Sc nursing groups. Conclusion: The present study showed that the BMI of first year students of MBBS course is higher than first year students of B Sc nursing course. J Dhaka Medical College, Vol. 28, No.1, April, 2019, Page 11-16